Promoting the well-being of higher education: Re-engineering of transnational nursing education - Naidoo, V.; Sibiya, M.N. (South African Journal of Higher Education, 2018)
Internationalization of nursing education has become a priority of academic institutions’ strategic plans and visions allowing for greater autonomy and inter-connectedness of the nursing profession. South African universities have, in recent years, engaged in international partnerships, influencing the delivery and facilitation of transnational nursing education (TNE) or cross-border nursing education, involving the steady increase of international student enrolment, particularly from other African nations. Whilst, much has been written about international partnerships relevant to other forms of higher education, minimal research has been done and reported on for cross-border nursing education and partnerships. This provided the rationale for this study to examine and explore TNE challenges by using actual participant examples and experiences. Using a qualitative, multiple case-study approach to sample local, national and international nursing education institutions, academic leaders and nurse graduates, the study attempted to identify challenges and best operating practices in TNE implementation and facilitation. The study aimed to highlight regulatory, administrative and quality assurance factors that challenged TNE’s successful delivery and findings revealed that these programmes are still challenged alluding to it being a ‘for profit’ arrangement. The study, further concluded that, for international students to adapt academically and socially and be in a position to fulfil the requirements of their respective academic programmes, a culturally and socially inclusive teaching and learning environment needed to be provided. This will ensure that the standard of the programme remained consistently high and globally competitive increasing the credibility of the educational institution and the country’s higher education system.